Application of Guitar Learning Methods to Reach Musicianship as Intercultural Activities in Formal and Non-Formal Institutions in West Sumatera - Handra Kadir, Tulus (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
This article reviews and analyses how methods, weaknesses, problems, solutions, and learning outcomes achieved in classical guitar learning at formal and non-formal educational institutions in West Sumatra as intercultural activities. Review and analysis refers to the principles, concepts, and methods of learning music, especially Western classical guitar, referred to throughout the world, namely the concept of Western music and the Yamaha Music Education System. The discussion in this article originates from the results of the first stage of the two planned research stages on the method of learning guitar instruments in formal and informal institutions in West Sumatra. The research method is qualitative and experimental. The first phase of the research is directed at finding, analyzing, and concluding methods of learning the practice of guitar instruments, their weaknesses, problems, and solutions to formal and informal institutions in West Sumatra. The second stage of the research is directed at finding and formulating weaknesses and shortcomings of guitar learning methods, then finding the need for guitar learning through analysis and assessment of guitar learning needs and then creating guitar learning methods based on 'sign' and 'interpretation' in the context of 'musicianship' and achievement of the learning objectives of the Major Guitar Instrument Practice course in the Music Education Study Program at the Faculty of Language and Art, Universitas Negeri Padang. Artikel ini mengkaji dan menganalisis bagaimana metode, kelemahan, permasalahan, solusi, dan capaian pembelajaran yang dicapai dalam pembelajaran gitar klasik di lembaga pendidikan formal dan nonformal di Sumatera Barat sebagai kegiatan antarbudaya. Kajian dan analisis mengacu pada prinsip, konsep, dan metode pembelajaran musik, khususnya gitar klasik Barat, yang dirujuk di seluruh dunia, yaitu konsep musik Barat dan Sistem Pendidikan Musik Yamaha. Pembahasan dalam artikel ini bersumber dari hasil tahap pertama dari dua tahap penelitian yang direncanakan tentang metode pembelajaran alat musik gitar di lembaga formal dan informal di Sumatera Barat. Metode penelitian yang digunakan adalah kualitatif dan eksperimental. Tahap pertama penelitian diarahkan untuk menemukan, menganalisis, dan menyimpulkan metode pembelajaran praktik alat musik gitar, kelemahan, permasalahan, dan solusinya pada lembaga formal dan informal di Sumatera Barat. Tahap kedua penelitian, diarahkan untuk menemukan dan merumuskan kelemahan dan kekurangan metode pembelajaran gitar, kemudian menemukan kebutuhan pembelajaran gitar melalui analisis dan penilaian kebutuhan pembelajaran gitar dan kemudian membuat metode pembelajaran gitar berbasis ‘tanda’ dan ‘interpretasi’ dalam konteks ‘musicianship’ dan pencapaian tujuan pembelajaran mata kuliah Praktik Instrumen Gitar Utama pada Program Studi Pendidikan Musik di Fakultas Bahasa dan Seni Universitas Negeri Padang.